2001
DOI: 10.1021/bc000099z
|View full text |Cite
|
Sign up to set email alerts
|

Diquaternary Ammonium Compounds as Transfection Agents

Abstract: Diquaternary ammonium salts constitute a new class of reagent for mediating transfection of DNA in mammalian cell lines. N,N'-dioleyl-N,N,N',N'-tetramethyl-1,2-ethanediamine (TmedEce), N,N'-dioleyl-N,N,N',N'-tetramethyl-1,3-propanediamine (PropEce), N,N'-dioleyl-N,N,N',N'-tetramethyl-1,6-hexanediamine (HexEce), and their corresponding N,N'-dicetyl saturated analogues (TmedAce, PropAce and HexAce) have all been synthesized and characterized. They were prepared via a bis-Menshutkin reaction of the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 19 publications
0
54
0
Order By: Relevance
“…Rosenzweig et al [40] found that certain 16-n-16 series of diquaternary ammonium compounds were capable of transfecting BHK-21 hamster kidney cells in vitro in the absence of DOPE. Transfection efficiency was highest for an intermediate spacer length 16-6-16; shorter spacers (2 or 3) were 5-10-fold less effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosenzweig et al [40] found that certain 16-n-16 series of diquaternary ammonium compounds were capable of transfecting BHK-21 hamster kidney cells in vitro in the absence of DOPE. Transfection efficiency was highest for an intermediate spacer length 16-6-16; shorter spacers (2 or 3) were 5-10-fold less effective.…”
Section: Discussionmentioning
confidence: 99%
“…DOPE inhibited transfection by the 16-2-16 gemini surfactant even at low amounts (2 : 1 gemini/DOPE ratio). The presence of serum also inhibited transfection efficiency by these gemini surfactants [40] leading to concerns about their utility in systemic gene therapy. However, our results in vivo indicate that this should not be a limiting factor for topical application.…”
Section: Discussionmentioning
confidence: 99%
“…the transport of genetic material through biological membranes into eukaryotic cells, are characteristic applications of green gemini surfactants [67,68]. Certain cationic gemini surfactants with low toxicity have a superior ability to introduce genes into cells [69][70][71][72]. pH regulation has profound effects on surface adsorption and aggregation behavior of gemini surfactants [73].…”
Section: Greenolution Of Industrial Needs By Using Cationic Geminismentioning
confidence: 99%
“…The use of the so-called nonviral vectors [4] makes it possible to solve problems connected with the condensation and compaction of giant DNA polyanions, with such limitations of viral vectors as immune response avoided. Although the application of synthetic vectors including those based on cationic surfactants and lipids is well documented [5][6][7], it is yet a challenging problem due to their relatively lower transfection efficacy compared to viral carriers. One of the main trends in the development of current protocols is the design of carriers with multicentered interactions with phosphate anions of DNA, including those based on gemini surfactants [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%